COMPOSITE ELECTROCHEMICAL COATINGS BASED ON CHROME, COPPER, ZINC, IRON, TIN, PRECIOUS METALS: OBTAINING, STRUCTURE, PROPERTIES (REVIEW) - Gab, Angelina; Malyshev, Victor; Shakhnin, Dmytro; Kuris, Yuri; Kyrychenko, Aleksiy; Vodennikova, Oksana; Volyar, Roman (Scientific Journal "Metallurgy", 2022)
One of the ways to improve the metal parts physical and mechanical properties is to deposit complex electrochemical coatings (CEC) onto them. The chromium current yield in the presence of ultrafine diamonds (UFD) is reduced in both standard and self-regulating chroming electrolytes. The microhardness of chromium – UFD CECs de-creases compared to pure chromium coatings from 1.03 GPa to 9.06 GPa (standard electrolyte) and from 9.68 GPa to 9.50 GPa (self-regulating electrolyte). Chromium-graphite composite coatings can be used in products operating under dry friction conditions. Self-lubricating chromium-graphite CECs can be obtained if the graphite content in the chromium solution is up to 4 g/L. Cerium dioxide containing chromium coatings deposited in the tetraethylamine presence have a very high wear resistance. The wear resistance and hardness of chromium-based CECs is significantly increased by introducing of silicon or titanium dioxide dispersed particles into the standard chroming electrolyte. The main purpose of copper-based CECs is provision of metal surfaces with wear resistance, heat resistance, and antifrictional properties. Sulfate electrolytes are most often used to obtain copper-based CECs. The UFD particles introduction into the electrolyte up to a concentration from 0.1 to 5.0 g/L does not change the nature and mechanism of the electrode process. The microhardness of coatings deposited from an electrolyte with UFD concentration 5.0 g/L increases almost one and a half times compared to the deposits obtained from the standard electrolyte. The copper – UFD CEC wearing degree is 9–10 times less than that of pure copper. Electrolytic iron coatings are used to restore parts of machines and mechanisms. Zinc-based composite coatings are used to protect steel surfaces from corrosion with simultaneous improvement of their physical and mechanical properties. Silver-based CECs with electrically conductive particles are deposited onto electrical contacts to improve their electrical conductivity.